SDS-Assisted Hydrothermal Growth and Photocatalytic Activity of Like-Caviar MoFe2O4 Nanoparticle Decorated with Al2O3 - Hameed, Mohammed Ali; Ahmed, Luma Majeed (Universitas Gadjah Mada, 2024)
Like-caviar molybdenum ferrite nanoparticles (MoFe2O4 NPs) have been successfully synthesized via a hydrothermal route in the presence of the negative surfactant (sodium dodecyl sulfate (SDS)). SDS acts as a template, stabilizer, and stops the aggregating process through storage. The mean crystal size of MoFe2O4 NPs rises with decorating it with Al2O3. Based on SEM analysis, the shapes of MoFe2O4, Al2O3, and their composite demonstrated like-caviar, like-brain cells, and like-grains, respectively. Al2O3 has been chosen to incorporate with spinel MoFe2O4 to make it color more light, this crucial step is necessary to enhance their optical characteristics. FTIR spectra observed the MoFe2O4 NPs are inverse spinel. The photo-decolorization test employs indigo carmine (IC) as a model pollutant. The quantum yields (Φ) of IC dye decolorization with studied photocatalysts are low, which may be created by quencher materials, dimerization of dye molecules, and photophysical deactivation processes (ISC process). Moreover, the photocatalytic activity of using MoFe2O4 raised after being decorated with alumina, which revealed an increase in the surface acidity, hydroxyl group adsorption, size, band gap, pHpzc of MoFe2O4 from 2.9–3.6 to 4.2–5.9 after decorated alumina. This pH is suitable for decolorizing IC dye, which has a pH of solution equal to 5.3.